Is COVID-19 Infection in Pregnancy A Risk Factor for Antepartum Fetal Compromise? A Case Series and Literature Review - A, Azaghdani; A, Opoku; ME, Gaber; FM, Balluz; L, Al-Ansari (Archives of Clinical and Medical Case Reports, 2021)
This case series explores whether COVID-19 infection is an independent risk factor for abnormal antepartum Cardiotocogram (CTG). We describe retrospective case reviews of nine pregnant women with confirmed COVID-19 infection who were admitted to Al Wakra Hospital, Qatar between April 1 and May 22, 2021. Each woman had a prelabour abnormal cardiotocogram (CTG) that necessitated delivery by emergency caesarean section. Five patients were admitted at less than 32 weeks gestation; the other four were 36 weeks or more. One had preeclampsia and gestational diabetes, another had gestational diabetes. Four patients were admitted with severe COVID-19 pneumonia, whereas the other five had mild COVID-19 symptoms. The four severe cases were on remdesivir and dexamethasone, including one on tocilizumab. Three patients were on hydroxychloroquine and the other two were on symptomatic treatments. Four patients were on supplemental oxygen. Regarding fetal outcome, five babies had APGAR Scores of less than 5 at one minute, but all babies had APGAR Scores above 7 at five minutes. Five babies had arterial pH less than 7.20, two of them less than 7.00. Five babies were intubated, and one was cooled. None of the babies had a positive COVID-19 reverse transcription polymerase chain reaction (RT-PCR) result. We conclude that COVID-19 infection in pregnancy could be an independent risk factor for abnormal antepartum CTG. This study is small and so more research is needed to further ascertain this finding. We recommend enhanced antenatal fetal surveillance using CTG for pregnant women admitted with COVID-19 infection.